Seorang Wanita Muda dengan Tuberkulosis Usus Menyerupai Apendiksitis Akut : [Pemphigus Paraneoplastic in Thymoma: A Rare Case] - Kadek Widianiti; Tutik Kusmiati; Ida Bagus Ngurah Rai (Faculty of Medicine Universitas Airlangga, 2018)
Background: Tuberculosis has become a global health problem, with increasing numbers of cases in line with the increasing number of immunocompromised patients. Intestinal of tuberculosis is believed to be a form of extrapulmonary tuberculosis which will occur most often in the future . Case: This case presents a young woman, 20 years old, suspected of acute appendicitis with suspected perforation, had right abdominal pain since 1 month and getting worse since 5 days PTA (prior to admission). The abdomen enlarges and feels hard on the right abdomen after being treated for 3 days. Fever,body weaknes,decreased of appetite, decreased of body weight approximately 7 kg since 2 months PTA. There are nausea, vomiting, diarea with runny mucus since 2 weeks PTA. The chest x-ray, abdominal ultrasound, endoscopy was normal result and plain abdominal radiograph showed that intestinal dilatation and step ladder features suspicious obstructive ileus. Discussion: After 2 months of therapy abdominal symptoms improved and weight began to gradually increase. Intestinal of tuberculosis is a challenge for clinicians to diagnose despite using modern medical techniques because the clinical and laboratory features are not specific especially when active pulmonary infection is absent and there are similarities with other abdominal diseases. The histological features will provide a diagnose. The delay in diagnosis will lead to more severe complications. Conclusion: At present a combination of clinical, radiological and pathological features continues to be the key to diagnosing intestinal tuberculosis. Medical management with antituberculosis drugs will produce a significant resolution of symptoms.